Bifunctional catalyst as well as preparation method and application thereof

Through the dual-function catalyst composed of Ni3Fe and Ti3C2, it is supported on the surface of Ti3C2, which solves the problem of low hydrogen storage and hydrolysis hydrogen production performance, achieves low temperature operation and high conversion rate, and improves the hydrogen storage and hydrogen production performance of magnesium.

CN119215944AActive Publication Date: 2024-12-31NANJING TECH UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411288859.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-31
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

In the prior art, the kinetic performance of magnesium hydrogen storage and hydrolysis hydrogen production is poor, and the existing catalyst is inconvenient to operate at high temperatures, and the amount of catalyst added is large, which makes the economy and portability insufficient.

Method used

A dual-function catalyst composed of Ni3Fe and Ti3C2 was used to prepare a supported structure of Ni3Fe particles supported on the surface of Ti3C2 by electrostatic composite and thermal reduction. It was used to reduce the operating temperature and improve the catalytic effect during magnesium hydrogen storage and hydrolysis hydrogen production.

Benefits of technology

It effectively reduces the hydrogen absorption temperature of magnesium hydrogen storage to 50℃, improves the conversion rate of hydrolysis hydrogen production to 94.7%, and meets applications in a wide temperature range, significantly improving the hydrogen storage and hydrogen production performance of magnesium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119215944A_ABST
    Figure CN119215944A_ABST
Patent Text Reader

Abstract

The invention provides a bifunctional catalyst as well as a preparation method and application thereof, and particularly relates to a bifunctional catalyst capable of improving both magnesium hydrogen storage performance and hydrogen production performance, the bifunctional catalyst comprises Ni3Fe and Ti3C2 in a mass ratio of (3-6): 1; the structure of the catalyst is a supported structure that Ni3Fe particles are supported on the surface of lamellar Ti3C2, and the catalyst has the advantages of being high in component interaction and excellent in supported substance dispersity. In the field of magnesium hydrogen storage, only 5 wt.% of the catalyst is needed, the effective hydrogen absorption temperature of magnesium hydrogen storage is reduced from 200 DEG C to 50 DEG C, and the dehydrogenation peak temperature is reduced from 384.5 DEG C to 279.9 DEG C. In the field of hydrogen production from magnesium, only 0.5 wt% of the catalyst is added, so that the conversion rate of hydrogen production from hydrolysis of magnesium within 30 seconds reaches 94.7%, and the practical application in a wider temperature range is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The present invention relates to a catalyst and a preparation method and application thereof, and in particular to a bifunctional catalyst capable of improving both hydrogen storage and hydrogen production performance of magnesium and a preparation method and application thereof. The material has the characteristics of strong interaction between components and excellent dispersion of supported materials, and can simultaneously improve the kinetic performance of the dual system of hydrogen storage and hydrogen production by hydrolysis of magnesium. Background technology:

[0002] Hydrogen energy has the advantages of high calorific value, zero pollution, and recyclability. It can convert hydrogen energy and electric energy through fuel cells to achieve large-scale peak load regulation of the power grid and cross-seasonal and cross-regional energy storage; it can also be converted into hydrogen energy and thermal energy by combustion. The final product of both types of energy conversion is only water, which can accelerate the low-carbonization of industries, construction, transportation and other fields. Hydrogen energy has the characteristics of recyclability, zero emissions, storage, and energy interconnection. Its efficient production and storage technology has received widespread attention, but due to the extremely low volume density of hydrogen, its portable storage has become the main constraint for hydrogen energy to enter the practical application stage and become popular.

[0003] Magnesium metal can absorb or release hydrogen by heating (pyrolysis), and its theoretical mass hydrogen storage density is as high as 7.6wt.%, which is much higher than most metal hydrogen storage materials. In addition, magnesium metal has high reserves in the earth's crust, is relatively cheap, and has good reversibility of hydrogen absorption and desorption reactions, so it can be applied to large-scale hydrogen storage stations and on-board hydrogen storage systems. However, the binding force between Mg and H is very strong, and the reaction activation energy that needs to be overcome for dehydrogenation is as high as 160kJ / mol. The high operating temperature and slow hydrogen absorption and desorption rate are the main factors restricting its practical application. In addition, magnesium metal can directly release hydrogen by hydrolysis (reaction with water), which can be applied to small-scale application scenarios of portable clean hydrogen sources. However, the kinetic performance of magnesium hydrolysis to produce hydrogen is very slow, and the conversion rate is low; and due to the non-recyclability of hydrolysis to produce hydrogen, the economy and portability of the system are very critical. Doping magnesium with trace amounts of transition metals through ball milling is an effective means to promote its hydrogen storage and hydrolysis hydrogen production performance, which can greatly improve the kinetic performance and avoid excessive loss of material capacity. Transition metal Ni-based materials are commonly used catalysts. Cheng et al. (Int J Hydrogen Energy, 2019, 44: 10777-87) deposited Pd and Ni nanoparticles on the surface and inside of mesoporous carbon by simple impregnation and high-temperature reduction. This bimetallic catalyst significantly improved the MgH 2Hydrogen storage performance, can release about 6wt% hydrogen at a temperature of 561K, but the price of metal Pd is relatively expensive. Yao et al. (J Phys Chem B, 2006, 110: 11697–703) found that compared with single element catalysts, the composite of FeTi and CNT has a more significant effect on the hydrogen absorption rate of Mg. The ternary composite of Mg-FeTi-CNT can absorb 5wt% hydrogen within 10min at 200°C, but the longer grinding time (30-60 hours) and higher hydrogen absorption temperature are not conducive to large-scale application. Transition metals and their oxides have a greater promoting effect on the hydrolysis performance of Mg. Huang et al. (Int. J. Hydrogen Energy, 2017, 42(35): 22305-11) reported that Fe 2 O 3 ,CaO,MoO 3 , Fe 3 O 4 , Nb 2 O 5 、TiO 2 The effect of Mg-MoO 3 and Mg-Fe 2 O 3 With up to 888mL g -1 min -1 The hydrogen production rate reaches 95.2% within 10 minutes.

[0004] Obviously, metal catalysts have shown excellent catalytic performance in both magnesium hydrogen storage systems and hydrogen production systems. However, few studies have developed a high-performance transition metal-based catalyst based on the commonality of hydrogen movement during magnesium hydrogen storage and hydrolysis hydrogen production, which has the dual function of promoting magnesium hydrogen storage performance and improving hydrolysis hydrogen production performance. In magnesium's large-scale hydrogen storage system, the current requirements for magnesium's hydrogen absorption and desorption temperatures are relatively high, and its performance modification should aim to reduce the operating temperature; in magnesium hydrolysis hydrogen production systems, due to the irreversible one-time characteristics of hydrolysis, its performance modification should focus on reducing the amount of catalyst added to meet economic efficiency. At present, in magnesium hydrogen storage systems, the catalytic effects of Ni and Fe are far from meeting the requirements of practical applications; in magnesium hydrogen production systems, due to the small specific surface area of ​​metal catalysts, low addition amounts cannot exhibit catalytic performance. Ti 3 C 2 As a two-dimensional material, it can greatly increase the specific surface area of ​​metal catalysts, but it is difficult for metal catalysts to be anchored on their surface, and metal loads usually show detachment and agglomeration phenomena. Summary of the invention:

[0005] The purpose of the present invention is to improve the existing technology to solve the problem of poor kinetic performance of magnesium hydrogen storage / hydrolysis hydrogen production and provide a bifunctional catalyst that improves both magnesium hydrogen storage and hydrogen production performance. Another purpose of the present invention is to provide a method for preparing the above catalyst. Another purpose of the present invention is to provide the application of the above catalyst. The catalyst component includes Ni 3 Fe and Ti 3 C 2 , mass ratio is 3 to 6:1; structure is Ni 3 Fe particles are loaded on the Ti lamellar 3 C 2 The supported structure on the surface has the characteristics of strong interaction between components and excellent dispersion of supported materials. The addition of 5wt.% of the catalyst reduces the effective hydrogen absorption temperature of magnesium hydrogen storage from 200℃ to 50℃, and the dehydrogenation peak temperature from 384.5℃ to 279.9℃. The addition of 0.5wt.% of the catalyst makes the conversion rate of magnesium hydrolysis to hydrogen within 30s reach 94.7%, and meets the practical application in a wide temperature range.

[0006] The technical solution adopted by the present invention is: a bifunctional catalyst, characterized in that the bifunctional catalyst component includes Ni 3 Fe and Ti 3 C 2 , mass ratio is 3 to 6:1; structure is Ni 3 Fe particles are loaded on the Ti lamellar 3 C 2 Surface load-bearing structure.

[0007] The present invention also provides a method for preparing the above-mentioned dual-function catalyst, wherein the preparation method is to electrostatically compound NiFe-LDH with Ti 3 C 2 The colloidal solution was centrifuged and dried to obtain the self-assembled (NiFe-LDH)-Ti 3 C 2 Precursor, followed by thermal reduction (NiFe-LDH)-Ti 3 C 2 Precursor obtains Ni 3 Fe-Ti 3 C 2 Bifunctional catalyst. Ni 3 Fe-Ti 3 C 2 With MgH 2 / Mg was compounded by ball milling process, and the corresponding hydrogen storage and hydrolysis hydrogen production performance tests proved that Ni 3 Fe-Ti 3 C 2 It has an excellent promoting effect on both the hydrogen storage and hydrogen production properties of magnesium and shows the synergistic catalytic characteristics between the catalyst components.

[0008] The specific steps are as follows:

[0009] (1) A certain proportion of Ni(NO 3 ) 2 6H 2 O, Fe(NO 3 ) 3 9H 2 O, urea and NH 4 F was added with methanol solution and mixed, and the mixture was solvent heated in a high pressure reactor for a certain period of time, and then centrifuged, washed and dried to obtain flower-shaped NiFe-LDH;

[0010] (2) Etching Ti 3 AlC 2 The product suspension was obtained, and then subjected to ultrasonic centrifugal stripping treatment, and the upper colloidal solution was collected to obtain Ti 3 C 2 Colloidal solutions;

[0011] (3) Add the NiFe-LDH in step (1) to the Ti in step (2) in batches. 3 C 2 The colloidal solution is then subjected to sealed ultrasonic dispersion, centrifugal washing and drying treatments to obtain (NiFe-LDH)-Ti 3 C 2 Precursor; (4) (NiFe-LDH)-Ti in step (3) 3 C 2 The precursor is calcined and reduced to obtain Ni 3 Fe-Ti 3 C 2 Bifunctional catalyst.

[0012] Preferably, in step (1), Ni(NO 3 ) 2 6H 2 O, Fe(NO 3 ) 3 9H 2 O, urea and NH 4 The molar ratio of F is 6:2:(12-15):(0.5-1); the solvent thermal temperature is 90-120°C, and the insulation time is 8-12h; the centrifugal washing speed is 6000-8000rpm, and the centrifugal washing time is 10-30min; the drying temperature is 40-50°C, and the drying time is 24-48h.

[0013] The product suspension in step (2) is etched with a LiF-HCl mixed solution according to the invention patent CN114843700A. 3 AlC 2Prepared by method.

[0014] The preferred parameters for the ultrasonic centrifugal stripping treatment in step (2) are: ultrasonic temperature of 0-5°C, ultrasonic power of 300-400W, ultrasonic treatment time of 1-3h; centrifugal stripping speed of 3000-4000rpm, and centrifugal stripping time of 1-3h.

[0015] Preferably, the number of times of division in step (3) is 8 to 10 times; the ultrasonic temperature is 0 to 5°C, the ultrasonic power is 300 to 400W, and the ultrasonic treatment time is 1 to 3h; the centrifugal washing speed is 6000 to 8000rpm, and the centrifugal washing time is 10 to 30min; the drying temperature is 40 to 50°C, and the drying time is 24 to 48h.

[0016] Preferably, the calcination reduction temperature in step (4) is 500-600° C., the calcination reduction time is 1-3 hours, and the calcination reduction atmosphere is pure hydrogen or a hydrogen-argon mixed gas with a hydrogen volume concentration of 5%-10%.

[0017] The present invention also provides the above-mentioned Ni 3 Fe-Ti 3 C 2 Application of bifunctional catalyst in metal hydrogen storage. Characterized by: Ni 3 Fe-Ti 3 C 2 With MgH 2 The mixture was mixed by ball milling. The ball milling loading and unloading process were carried out in an argon atmosphere glove box. The added mass of the catalyst was MgH 2 and 3% to 10% of the total mass of the catalyst. The present invention also provides the above-mentioned Ni 3 Fe-Ti 3 C 2 Application of bifunctional catalyst in metal hydrogen production. Characteristic: Ni 3 Fe-Ti 3 C 2 The catalyst is mixed with Mg by ball milling, and the ball milling loading and unloading processes are all carried out in an argon atmosphere glove box, and the catalyst accounts for 0.5wt.% to 8wt.% of the total mass of Mg and the catalyst.

[0018] The NiFe-LDH prepared by the present invention is positively charged in the solution. 3 C 2 The colloidal solution is negatively charged. A certain amount of NiFe-LDH is slowly added to Ti 3 C 2 The solution can be self-assembled into NiFe-LDH by electrostatic adsorption and loaded on Ti 3 C 2The supported structure on the surface is further calcined in a reducing atmosphere to obtain supported Ni 3 Fe-Ti 3 C 2 Catalyst. Ni 3 Fe and Ti 3 C 2 The components show synergistic catalytic effects. This catalyst greatly reduces the operating temperature in the process of magnesium hydrogen storage, and greatly improves the hydrogen production rate and conversion rate in the process of magnesium hydrolysis to produce hydrogen, showing a dual-functional catalytic effect of promoting magnesium hydrogen storage / hydrogen production at the same time.

[0019] Beneficial effects:

[0020] (1) Compared with the common metal catalyst loading system, the bifunctional catalyst provided by the electrostatic self-assembled precursor of the present invention has the characteristics of strong interaction between components, excellent dispersion without the load falling off.

[0021] (2) Compared with the single function of common catalysts (hydrogen storage or hydrolysis hydrogen production system), the bifunctional catalyst provided by the present invention exhibits a synergistic effect of components through a supported structure, thereby having a strong catalytic effect of both magnesium hydrogen storage and hydrolysis hydrogen production.

[0022] (3)Ni 3 Fe-Ti 3 C 2 The bifunctional catalyst reduces the operating temperature of magnesium hydrogen absorption from 200°C to 50°C, and the hydrogen absorption capacity is as high as 4.56wt.%, providing broad prospects for the application of magnesium hydrogen storage systems.

[0023] (4) Only 0.5wt.% Ni is required 3 Fe-Ti 3 C 2 The bifunctional catalyst enables the conversion rate of micron magnesium to hydrogen production by hydrolysis to reach 94.7% within 30 seconds; at the same time, it meets a wide range of hydrolysis temperatures and meets the actual use requirements of metal hydrolysis to produce hydrogen. Description of the drawings:

[0024] Figure 1 Ni prepared in Examples 1 to 4 3 Fe-Ti 3 C 2 (Ni 3 Fe and Ti 3 C 2 XRD patterns of bifunctional catalysts with a mass ratio of 3:1, 4:1, 5:1, and 6:1;

[0025] Figure 2 MgH prepared in Application Example 2 2 -5 wt.%Ni 3 Fe-Ti3 C 2 (Ni 3 Fe and Ti 3 C 2 DSC curves of mass ratios of 3:1, 4:1, 5:1, 6:1);

[0026] Figure 3 (NiFe-LDH)-Ti prepared in Example 3 3 C 2 Precursor (a) and Ni 3 Fe-Ti 3 C 2 (5:1)(b) SEM image of the sample;

[0027] Figure 4 MgH prepared in Application Example 3 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 (5:1) and the DSC curves of the samples of Comparative Example 1, Comparative Example 2 and Comparative Example 3;

[0028] Figure 5 MgH prepared in Application Example 3 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 (5:1) Isothermal hydrogen absorption curves at different temperatures compared with Comparative Example 3;

[0029] Figure 6 Mg-y wt.%Ni prepared in Application Example 4 3 Fe-Ti 3 C 2 (5:1)(y=0.5,1,2,5,8) Hydrolysis hydrogen production curve at 30℃;

[0030] Figure 7 Mg-5wt.%Ni prepared in Application Example 5 3 Fe-Ti 3 C 2 (5:1) Hydrogen production curves by hydrolysis at different temperatures;

[0031] Figure 8 Mg-5wt.%Ni prepared in Application Example 5 3 Fe-Ti 3 C 2 (5:1) and the hydrolysis hydrogen production curves of the samples of Comparative Example 4, Comparative Example 5 and Comparative Example 6 at 0°C. Specific implementation method:

[0032] The present invention is further described in detail below in conjunction with specific implementation methods. The given embodiments and application examples are only for illustrating the present invention, rather than for limiting the scope of the present invention.

[0033] The experimental methods in the following embodiments and application examples are conventional methods unless otherwise specified.

[0034] Unless otherwise specified, the materials, reagents, etc. used in the following embodiments and application examples can be obtained from commercial sources.

[0035] Example 1

[0036] (1) 6 mmol Ni(NO 3 ) 2 6H 2 O, 2mmol Fe(NO 3 ) 3 9H 2 O, 12mmol urea and 0.5mmol NH 4 F was added into 50 ml methanol solution, dissolved, sealed in a reaction kettle and reacted at 120°C for 8 h. After the reaction, the product was washed three times by alternating centrifugation with deionized water and ethanol, wherein the centrifugal speed was 6000 rpm and the centrifugal time was 30 min. Then, NiFe-LDH was obtained by drying in an oven at 40°C for 24 h.

[0037] (2) Referring to Example 1 of the invention patent CN114843700A, 2 g of LiF was added to 40 mL of 9 M HCl which was stirred continuously, and then 2 g of Ti was added thereto. 3 AlC 2 Then, the above solution was placed in a 40°C water bath and stirred for 24 hours to obtain an etching product, which was then washed with ultrapure water until the pH value was 6.

[0038] (3) The above product was sealed at 5°C, ultrasonicated at 300W for 3h, centrifuged at 4000rpm for 1h, and the upper dark green solution of the product was collected as the obtained Ti 3 C 2 Colloidal solution.

[0039] (4) According to Ni 3 Fe and Ti 3 C 2 The mass ratio of NiFe-LDH was 3:1, and NiFe-LDH was added to Ti in 8 portions with stirring. 3 C 2 The solution was sealed at 5 °C, ultrasonically dispersed at 300 W for 3 h, centrifuged at 6000 rpm for 30 min, and then dried in an oven at 40 °C for 24 h to obtain (NiFe-LDH)-Ti 3 C2 Catalyst Precursors.

[0040] (5) Then the above (NiFe-LDH)-Ti 3 C 2 The catalyst precursor was calcined in a hydrogen atmosphere at 500 °C for 1 h to obtain Ni 3 Fe-Ti 3 C 2 (3:1) catalyst.

[0041] Example 2

[0042] (1) 6 mmol Ni(NO 3 ) 2 6H 2 O, 2mmol Fe(NO 3 ) 3 9H 2 O, 13mmol urea and 0.7mmol NH 4 F was added into 50 ml of methanol solution, dissolved and sealed in a reactor and reacted at 100°C for 10 h. After the reaction, the product was washed three times by alternating centrifugation with deionized water and ethanol, with a centrifugal speed of 7000 rpm and a centrifugal time of 25 min. It was then dried in an oven at 40°C for 48 h to obtain NiFe-LDH.

[0043] (2) Referring to Example 2 of the invention patent CN114843700A, 2 g of LiF was added to 40 mL of 9 M HCl which was stirred continuously, and then 2 g of Ti was added thereto. 3 AlC 2 Then, the above solution was placed in a 35°C water bath and stirred for 30 hours to obtain an etching product, which was then washed with ultrapure water until the pH value was 6.

[0044] (3) The above solution was sealed at 3°C, ultrasonicated at 350W for 2h, centrifuged at 3500rpm for 2h, and the upper dark green solution of the product was collected as the obtained Ti 3 C 2 Colloidal solution.

[0045] (4) According to Ni 3 Fe and Ti 3 C 2 The mass ratio of NiFe-LDH was 4:1, and NiFe-LDH was added to Ti in 9 times with stirring. 3 C 2 The colloid solution was sealed at 3°C, ultrasonically dispersed at 350W for 2h, centrifuged at 7000rpm for 25min, and then dried in an oven at 40°C for 48h to obtain (NiFe-LDH)-Ti 3 C 2Catalyst Precursors.

[0046] (5) Then the above (NiFe-LDH)-Ti 3 C 2 The catalyst precursor was placed in a hydrogen-argon mixed atmosphere (hydrogen volume concentration of 5%) at 550°C and calcined for 1 h to obtain Ni 3 Fe-Ti 3 C 2 (4:1) catalyst.

[0047] Example 3

[0048] (1) 6 mmol Ni(NO 3 ) 2 6H 2 O, 2mmol Fe(NO 3 ) 3 9H 2 O, 14mmol urea and 0.8mmol NH 4 F was added into 50 ml of methanol solution, dissolved, sealed and reacted in a reactor at 90°C for 12 h. After the reaction, the product was washed three times by alternating centrifugation with deionized water and ethanol, with a centrifugal speed of 8000 rpm and a centrifugal time of 10 min. The product was then dried in an oven at 50°C for 24 h to obtain NiFe-LDH.

[0049] (2) Referring to Example 3 of the invention patent CN114843700A, 2 g of LiF was added to 40 mL of 9 M HCl which was stirred continuously, and then 2 g of Ti was added thereto. 3 AlC 2 Then, the above solution was placed in a 45°C water bath and stirred for 20 hours to obtain an etching product, which was then washed with ultrapure water until the pH value was 7.

[0050] (3) The above solution was sealed at 0°C, ultrasonicated at 400W for 1h, centrifuged at 3000rpm for 3h, and the upper dark green solution of the product was collected as the obtained Ti 3 C 2 Colloidal solution.

[0051] (4) According to Ni 3 Fe and Ti 3 C 2 The mass ratio of NiFe-LDH was 5:1, and NiFe-LDH was added to Ti in 10 portions with stirring. 3 C 2 The colloid solution was sealed at 0°C, ultrasonically dispersed at 400 W for 1 h, centrifuged at 8000 rpm for 10 min, and then dried in an oven at 50°C for 24 h to obtain (NiFe-LDH)-Ti 3 C 2Catalyst Precursors.

[0052] (5) Then the above (NiFe-LDH)-Ti 3 C 2 The catalyst precursor was placed in a hydrogen-argon mixed atmosphere (hydrogen volume concentration was 10%) at 600°C and calcined for 2 h to obtain Ni 3 Fe-Ti 3 C 2 (5:1) catalyst.

[0053] Example 4

[0054] (1) 6 mmol Ni(NO 3 ) 2 6H 2 O, 2mmol Fe(NO 3 ) 3 9H 2 O, 15mmol urea and 1mmol NH 4 F was added into 50 ml of methanol solution, dissolved, sealed in a reactor and reacted at 110°C for 9 h. After the reaction, the product was washed three times by alternating centrifugation with deionized water and ethanol, wherein the centrifugal speed was 7000 rpm and the centrifugal time was 20 min. Then, NiFe-LDH was obtained by drying in an oven at 45°C for 36 h.

[0055] (2) Referring to Example 4 of the invention patent CN114843700A, 2 g of LiF was added to 40 mL of 9 M HCl which was stirred continuously, and then 2 g of Ti was added thereto. 3 AlC 2 Then, the above solution was placed in a 40°C water bath and stirred for 24 hours to obtain an etching product, which was then washed with ultrapure water until the pH value was 6.

[0056] (3) The above solution was sealed at 1°C, ultrasonicated at 350W for 3h, centrifuged at 3500rpm for 3h, and the upper dark green solution of the product was collected as the obtained Ti 3 C 2 Colloidal solution.

[0057] (4) According to Ni 3 Fe and Ti 3 C 2 The mass ratio of NiFe-LDH was 6:1, and NiFe-LDH was added to Ti in 10 portions with stirring. 3 C 2 The colloid solution was sealed at 1°C, ultrasonically dispersed at 350W for 3h, centrifuged at 7000rpm for 20min, and then dried in an oven at 45°C for 36h to obtain (NiFe-LDH)-Ti 3 C 2Catalyst Precursors.

[0058] (5) Then the above (NiFe-LDH)-Ti 3 C 2 The catalyst precursor was placed in a hydrogen-argon mixed atmosphere (hydrogen volume concentration of 10%) at 550°C and calcined for 3 h to obtain Ni 3 Fe-Ti 3 C 2 (6:1) Catalyst.

[0059] The results are as follows:

[0060] Figure 1 To thermally reduce the (NiFe-LDH)-Ti prepared in Examples 1-4 above 3 C 2 Catalyst precursor product Ni 3 Fe-Ti 3 C 2 (Ni 3 Fe and Ti 3 C 2 The XRD diagram of the mass ratio of 3:1, 4:1, 5:1, 6:1) shows that Ni 3 Fe and Ti 3 C 2 The characteristic diffraction peaks of different proportions of Ni 3 Fe-Ti 3 C 2 Successfully obtained.

[0061] Application Example 1

[0062] (1) Preparation of MgH by ball milling 2 -x wt.%Ni 3 Fe-Ti 3 C 2 (3:1)(x=3,5,8,10) Hydrogen storage material: Ni prepared in Example 1 3 Fe-Ti 3 C 2 (3:1) with MgH 2 By ball milling, MgH 2 with Ni 3 Fe-Ti 3 C 2 The mass ratios of the (3:1) bifunctional catalysts were 97:3, 95:5, 92:8, and 90:10, respectively. The ball milling time was 10 h, the ball-to-material mass ratio was 30:1, the ball milling speed was 400 r / min, and the milling was performed alternately with running for 30 minutes and stopping for 6 minutes. The ball milling loading and unloading processes were carried out in an argon atmosphere glove box.

[0063] (2) The composite hydrogen storage material prepared above was subjected to DSC test. The test conditions were: the mass of each test sample was 10 mg, the test atmosphere was argon atmosphere, the pressure was 27 kPa, and the heating rate was 10 °C / min. Combining the kinetic performance and hydrogen storage capacity, the DSC results showed that MgH 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 (3:1) shows the best hydrogen storage performance. 2 When the mass ratio of the bifunctional catalyst to the catalyst is 95:5, that is, the catalyst content is 5 wt.%, it is preferred.

[0064] Application Example 2

[0065] Preparation of MgH by ball milling 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 (Ni 3 Fe and Ti 3 C 2 The mass ratio is 3:1, 4:1, 5:1, 6:1) Hydrogen storage material: Take the Ni prepared in the above examples 1-4 3 Fe-Ti 3 C 2 (Ni 3 Fe and Ti 3 C 2 The mass ratio of MgH 2 By ball milling, MgH 2 and Ni 3 Fe-Ti 3 C 2 (Ni 3 Fe and Ti 3 C 2 The mass ratio of the bifunctional catalyst is 3:1, 4:1, 5:1, 6:1), the mass ratio of the bifunctional catalyst is 95:5, the ball milling time is 10 hours, the ball-to-material mass ratio is 30:1, the ball milling speed is 400r / min, and the operation is carried out for 30 minutes and 6 minutes of rest alternately. The ball milling loading and unloading processes are carried out in an argon atmosphere glove box.

[0066] Figure 2 MgH 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 (Ni 3 Fe and Ti 3 C 2The DSC curves of MgH 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 The dehydrogenation peak temperatures of (3:1) are 274.9℃ and 347.7℃ respectively; MgH 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 The dehydrogenation peak temperatures of (4:1) are 278.7℃ and

[0067] 339.9℃;MgH 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 The dehydrogenation peak temperatures of (6:1) are at 276.9°C and 301.2°C, respectively; while MgH 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 (5:1) has the best dehydrogenation performance, with only one peak dehydrogenation temperature, which is only 279.9°C. 3 Fe-Ti 3 C 2 The (5:1) bifunctional catalyst performed best.

[0068] Figure 3 (NiFe-LDH)-Ti 3 C 2 Catalyst precursor and Ni 3 Fe-Ti 3 C 2 (5:1) SEM image of the catalyst. The SEM image shows that Ti 3 C 2 It is a lamellar structure, with Ni of about 1 to 2 μm 3 Fe micron particles are loaded on the Ti lamellar 3 C 2 A load-bearing structure is formed on it.

[0069] Application Example 3

[0070] (1) Preparation of MgH by ball milling 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 (5:1) Hydrogen storage material: Ni prepared in Example 3 above 3 Fe-Ti 3 C 2 (5:1) with MgH2 By ball milling, MgH 2 and Ni 3 Fe-Ti 3 C 2 The mass ratio of the (5:1) bifunctional catalyst was 95:5, the ball milling time was 10 hours, the ball-to-material mass ratio was 30:1, the ball milling speed was 400 r / min, and the milling was performed alternately of running for 30 minutes and stopping for 6 minutes. The ball milling loading and unloading processes were carried out in an argon atmosphere glove box.

[0071] (2) The composite hydrogen storage material prepared above was subjected to DSC test, and the test conditions were: the mass of the sample for each test was 10 mg, the test atmosphere was argon atmosphere, the pressure was 27 kPa, and the heating rate was 10°C / min.

[0072] (3) The composite hydrogen storage material prepared above was subjected to an isothermal hydrogen absorption test. The test conditions were: the isothermal hydrogen absorption test temperature was 50, 100, and 150° C., and the hydrogen absorption pressure was 3 MPa.

[0073] The results are as follows:

[0074] Figure 4 For the prepared MgH 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 (5:1) and MgH in Comparative Example 1 2 -5 wt.%Ni 3 Fe, MgH in Comparative Example 2 2 -5 wt.%Ti 3 C 2 and MgH in Comparative Example 3 2 DSC curve of MgH 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 (5:1) has the best performance, with a dehydrogenation peak temperature of 279.9 °C, while MgH 2 -5 wt.%Ni 3 Fe and MgH 2 -5 wt.%Ti 3 C 2 The dehydrogenation peak temperatures of MgH 2 The dehydrogenation peak temperature is as high as 384.5°C. 3 Fe-Ti 3 C 2 The components show synergistic effect.

[0075] Figure 5 For the prepared MgH 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 (5:1) and MgH in Comparative Example 3 2 Isothermal hydrogen absorption curve. As can be seen from the figure, at 50℃, MgH 2 -5 wt.%Ni 3 Fe-Ti 3 C 2 (5:1) can achieve a hydrogen uptake of ~4.56 wt.%, while the catalyst-free MgH 2 It exhibits effective hydrogen absorption performance only at 200°C.

[0076] Application Example 4

[0077] (1) Preparation of Mg-y wt.%Ni by ball milling 3 Fe-Ti 3 C 2 (5:1)(y=0.5,1,2,5,8) Hydrolysis hydrogen production material: Take the Ni prepared in Example 3 above 3 Fe-Ti 3 C 2 (5:1) catalyst and Mg were mixed by ball milling, and Mg and Ni 3 Fe-Ti 3 C 2 The mass ratios of the (5:1) bifunctional catalysts were 99.5:0.5, 99:1, 98:2, 95:5 and 92:8, respectively. The ball milling time was 1 hour, the ball-to-material mass ratio was 30:1, the ball milling speed was 400 r / min, and the milling was performed alternately with running for 30 minutes and stopping for 6 minutes. The ball milling loading and unloading processes were carried out in an argon atmosphere glove box.

[0078] (2) The above hydrolysis hydrogen production material was placed in a 3.5% NaCl solution at 30°C to test its hydrolysis hydrogen production performance. The results are as follows:

[0079] Figure 6 Mg-y wt.%Ni 3 Fe-Ti 3 C 2 (5:1)(y=0.5,1,2,5,8)hydrolysis hydrogen production curve at 30℃; where Mg-0.5wt.%Ni 3 Fe-Ti 3 C 2 (5:1) reached a saturated hydrogen production of 873.3 mL / g in only 30 s, Mg-1wt.%Ni 3 Fe-Ti 3 C 2(5:1) reached saturated hydrogen production of 877.4 mL / g within 25 s, Mg-2wt.%Ni 3 Fe-Ti 3 C 2 (5:1) reached saturated hydrogen production of 873.2 mL / g within 25 s; Mg-5wt.%Ni 3 Fe-Ti 3 C 2 (5:1) reached saturated hydrogen production of 866.5 mL / g within 25 s; Mg-8 wt. % Ni 3 Fe-Ti 3 C 2 (5:1) reached a saturated hydrogen production of 843.8 mL / g within 25 s. Therefore, only 0.5 wt.% Ni 3 Fe-Ti 3 C 2 This enables magnesium to exhibit sufficiently efficient hydrolysis and hydrogen production performance.

[0080] Application Example 5

[0081] (1) Preparation of Mg-5wt.%Ni by ball milling 3 Fe-Ti 3 C 2 (5:1) Hydrolysis hydrogen production material: Take the Ni prepared in Example 3 above 3 Fe-Ti 3 C 2 (5:1) catalyst and Mg were mixed by ball milling, and Mg and Ni 3 Fe-Ti 3 C 2 The mass ratio of the (5:1) bifunctional catalyst was 95:5, the ball milling time was 1 hour, the ball-to-material mass ratio was 30:1, the ball milling speed was 400 r / min, and the milling was performed alternately of running for 30 minutes and stopping for 6 minutes. The ball milling loading and unloading processes were carried out in an argon atmosphere glove box.

[0082] (2) The above hydrolysis hydrogen production material was placed in 3.5% NaCl solution at 0, 10, 20, 30 and 40° C. to test its hydrolysis hydrogen production performance.

[0083] The results are as follows:

[0084] Figure 7 The prepared Mg-5wt.%Ni 3 Fe-Ti 3 C 2 (5:1) Hydrogen production curves by hydrolysis at different temperatures; Mg-5wt.%Ni 3 Fe-Ti 3 C 2(5:1) At 0, 10, 20, 30 and 40 °C, 835.6, 863.8, 865.2, 865.6 and 867.3 mL / g of hydrogen were produced within 15 s, respectively. 3 Fe-Ti 3 C 2 (5:1) still shows excellent hydrolysis hydrogen production performance.

[0085] Figure 8 The prepared Mg-5wt.%Ni 3 Fe-Ti 3 C 2 (5:1) and Mg-5wt.%Ni in Comparative Example 4 3 Fe, Mg-5wt.%Ti in Comparative Example 5 3 C 2 The hydrolysis hydrogen production curve of the Mg sample in Comparative Example 6; it can be seen from the figure that at 0°C, Mg-5wt.%Ni 3 Fe-Ti 3 C 2 (5:1) had the best hydrogen production performance by hydrolysis, producing 857.4 mL / g of hydrogen within 20 s. 3 Fe, Mg-5wt.%Ti 3 C 2 The Ni and Mg samples produced only 690.5, 49.3, and 27.7 mL / g of hydrogen, respectively. 3 Fe-Ti 3 C 2 Shows excellent synergistic effect of components.

[0086] Comparative Example 1:

[0087] (1)Ni 3 Preparation of Fe catalyst: 6 mmol Ni(NO 3 ) 2 6H 2 O, 2mmol Fe(NO 3 ) 3 9H 2 O, 14mmol urea and 1mmol NH 4 F was added to 50 ml of methanol solution, dissolved, sealed in a reactor and reacted at 90°C for 12 hours. After the reaction, the product was washed three times with deionized water and ethanol alternately by centrifugation, wherein the centrifugal speed was 6000 rpm and the centrifugal time was 30 min. Then, NiFe-LDH was dried in an oven at 40°C for 24 hours. Then, NiFe-LDH was calcined at 500°C in a hydrogen atmosphere for 1 hour to obtain Ni3 Fe catalyst.

[0088] (2) Preparation of MgH by ball milling 2 -5 wt.%Ni 3 Fe hydrogen storage material: Ni 3 Fe catalyst and MgH 2 By ball milling, MgH 2 and Ni 3 The mass ratio of Fe catalyst was 95:5, the ball milling time was 10 hours, the ball-to-material mass ratio was 30:1, the ball milling speed was 400 r / min, and the milling was performed alternately of running for 30 minutes and stopping for 6 minutes. The ball milling loading and unloading processes were carried out in an argon atmosphere glove box.

[0089] Comparative Example 2:

[0090] (1) Ti 3 C 2 Catalyst preparation: Ti 3 C 2 The colloidal solution was filtered and dried in an oven at 40°C for 24 hours.

[0091] (2) Preparation of MgH by ball milling 2 -5 wt.%Ti 3 C 2 Hydrogen storage material: Ti 3 C 2 Catalyst and MgH 2 By ball milling, MgH 2 and Ti 3 C 2 The catalyst mass ratio was 95:5, the ball milling time was 10 hours, the ball-to-material mass ratio was 30:1, the ball milling speed was 400 r / min, and the milling was performed alternately of running for 30 minutes and stopping for 6 minutes. The ball milling loading and unloading processes were carried out in an argon atmosphere glove box.

[0092] Comparative Example 3:

[0093] Preparation of MgH by ball milling 2 Hydrogen storage material: The ball milling time was 10 hours, the ball-to-material mass ratio was 30:1, the ball milling speed was 400 r / min, and the milling process was performed alternately of running for 30 minutes and stopping for 6 minutes. The ball milling loading and unloading processes were carried out in an argon atmosphere glove box.

[0094] Comparative Example 4:

[0095] Preparation of Mg-5wt.%Ni by ball milling 3 Fe hydrolysis hydrogen production material: Ni 3 Fe catalyst and Mg were mixed by ball milling, and Mg and Ni 3The mass ratio of Fe catalyst was 95:5, the ball milling time was 1 hour, the ball-to-material mass ratio was 30:1, the ball milling speed was 400 r / min, and the milling was performed alternately of running for 30 minutes and stopping for 6 minutes. The ball milling loading and unloading processes were carried out in an argon atmosphere glove box.

[0096] Comparative Example 5

[0097] Preparation of Mg-5wt.%Ti by ball milling 3 C 2 Hydrogen production materials: Ti 3 C 2 The catalyst and Mg were mixed by ball milling, and Mg and Ti 3 C 2 The catalyst mass ratio was 95:5, the ball milling time was 1 hour, the ball-to-material mass ratio was 30:1, the ball milling speed was 400 r / min, and the milling was performed alternately of 30 minutes of operation and 6 minutes of rest. The ball milling loading and unloading processes were carried out in an argon atmosphere glove box.

[0098] Comparative Example 6

[0099] Preparation of Mg hydrolysis hydrogen production material by ball milling: the ball milling time was 1 h, the ball-to-material mass ratio was 30:1, the ball milling speed was 400 r / min, and the milling was performed alternately of running for 30 minutes and stopping for 6 minutes. The ball milling loading and unloading processes were carried out in an argon atmosphere glove box.

Claims

1. A bifunctional catalyst, characterized in that: The bifunctional catalyst components include Ni3Fe and Ti3C2, with a mass ratio of 3 to 6:1; the structure is a supported structure in which Ni3Fe particles are supported on the surface of Ti3C2 sheets.

2. A method for preparing the bifunctional catalyst as claimed in claim 1, wherein the specific steps are as follows: (1) A certain proportion of Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, urea and NH4F were added to a methanol solution and mixed, and then solvent-heated in a high-pressure reactor for a certain period of time, and then centrifuged, washed and dried to obtain a flower-shaped NiFe-LDH; (2) etching Ti3AlC2 to obtain a product suspension, then performing an ultrasonic centrifugal stripping treatment, and collecting an upper colloidal solution to obtain a Ti3C2 colloidal solution; (3) adding the NiFe-LDH in step (1) to the Ti3C2 colloidal solution in step (2) in portions, and then performing sealed ultrasonic dispersion, centrifugal washing and drying treatment in sequence to obtain a (NiFe-LDH)-Ti3C2 precursor; (4) The (NiFe-LDH)-Ti3C2 precursor in step (3) is subjected to calcination reduction treatment to obtain a Ni3Fe-Ti3C2 bifunctional catalyst.

3. The method according to claim 2, characterized in that In step (1), the molar ratio of Ni(NO3)2·6H2O, Fe(NO3)3·9H2O, urea and NH4F is 6:2:(12-15):(0.5-1); the solvent thermal temperature is 90-120°C, and the insulation time is 8-12h; the centrifugal washing speed is 6000-8000rpm, and the centrifugal washing time is 10-30min; the drying temperature is 40-50°C, and the drying time is 24-48h.

4. The method according to claim 2, characterized in that The ultrasonic centrifugal stripping treatment parameters in step (2) are: ultrasonic temperature is 0-5°C, ultrasonic power is 300-400W, ultrasonic treatment time is 1-3h; centrifugal stripping speed is 3000-4000rpm, and centrifugal stripping time is 1-3h.

5. The method according to claim 2, characterized in that The number of times in step (3) is 8 to 10 times; the ultrasonic temperature is 0 to 5°C, the ultrasonic power is 300 to 400W, and the ultrasonic treatment time is 1 to 3 hours; the centrifugal washing speed is 6000 to 8000rpm, and the centrifugal washing time is 10 to 30 minutes; the drying temperature is 40 to 50°C, and the drying time is 24 to 48 hours.

6. The method according to claim 2, characterized in that In the step (4), the calcination reduction temperature is 500-600° C., the calcination reduction time is 1-3 hours, and the calcination reduction atmosphere is pure hydrogen or a hydrogen-argon mixed gas with a hydrogen volume concentration of 5%-10%.

7. Use of the Ni3Fe-Ti3C2 bifunctional catalyst as claimed in claim 1 in metal hydrogen storage.

8. The use according to claim 7, characterized in that: Ni3Fe-Ti3C2 and MgH2 are mixed by ball milling, and the ball milling loading and unloading processes are all carried out in an argon atmosphere glove box, wherein the added mass of the catalyst is 3% to 10% of the total mass of MgH2 and the catalyst.

9. Use of the Ni3Fe-Ti3C2 bifunctional catalyst as claimed in claim 1 in metal hydrogen production.

10. The use of the Ni3Fe-Ti3C2 bifunctional catalyst in metal hydrogen production according to claim 7, characterized in that: Ni3Fe-Ti3C2 and Mg are mixed by ball milling. The ball milling loading and unloading processes are carried out in an argon atmosphere glove box. The catalyst accounts for 0.5wt.% to 8wt.% of the total mass of Mg and the catalyst.

Citation Information

Patent Citations

  • MXene-loaded Ni@C nanoparticle hydrogen storage catalyst and preparation method thereof

    CN113546656A

  • Hydrolysis hydrogen production method based on magnesium-based composite material

    CN113562694A

  • Magnesium-based hydrogen storage material catalyzed by hexagonal boron nitride loaded nano nickel particles and preparation method of magnesium-based hydrogen storage material

    CN115231514A

  • Hydrogen storage material of LDH and MXene composite modified magnesium hydride and preparation method of hydrogen storage material

    CN115285935A

  • Bimetal nitride catalyst as well as preparation method and application thereof

    CN116786151A